Draws and Drawbacks of an Oxford Study Abroad Experience - Firmin, Michael W. (Journal of Interdisciplinary Studies in Education, 2019)
Using qualitative research methodology, we interviewed 23 American students participating in a study abroad program at Oxford University in the U.K.  Results showed four primary draws to participating in the study abroad program and two perceived drawbacks. Positively, Oxford’s first appealing dynamic related to the tutorial system and students’ expanded range of options for specialized topics as well as in-depth study. Next, participants highly valued Oxford’s academic rigor, which accompanied the university’s unique approach to education. Third, Oxford’s location in England appealed to our participants. Finally, students reported hopes that future benefits would result from their decisions to attend Oxford and perceived associations with Oxford’s prestige.  As participants weighed these benefits of studying at OU, they contrasted the positive dynamics with two major drawbacks: finances and missed U.S. experiences. Nevertheless, our participants unanimously affirmed their respective decisions to study at Oxford and highly recommended the experience to future potential applicants.